Synthesis of carbon nanofibers for mediatorless sensitive detection of NADH - Liu, Yang; Hou, H.; You, T. (Wiley - VCH Verlag GmbH & Co. KGaA, 2008)
Highly sensitive amperometric detection of dihydronicotinamide adenine dinucleotide (NADH) by using novel synthesized carbon nanofibers (CNFs) without addition of any mediator has been proposed. The CNFs were prepared by combination of electrospinning technique with thermal treatment method and were applied without any oxidation pretreatment to construct the electrochemical sensor. In amperometric detection of NADH, a linear range up to 11.45 μM with a low detection limit of 20 nM was obtained with the CNF-modified carbon paste electrode (CNF-CPE). Good selectivity was exhibited for the simultaneous detection of NADH and its common interferent of ascorbic acid (AA) by differential pulse voltammogram. The attractive electrochemical performance and the versatile preparation process of the CNF-CPE made it a promising candidate for designing effective NADH sensor.